Catalytic Performance of Copper-Manganese Supported on Activated Carbon Synthesized by Deposition-Precipitation Method - Melody, Kimi; Bibie Nur Syafiqah, Safiuddin; Suh, Cem Pang (Lviv Polytechnic National University, Lviv, 2020)
CuMnx/activated carbon (AC, x = 0.1, 0.2, 0.5 and 1) nanoparticles were prepared by deposition-precipitation method. The catalytic performance of CuMnx/AC catalysts were studied for the oxidation of benzyl alcohol to benzaldehyde. The molar ratio of Mn plays an important role in the catalytic performances. The optimum amount of Mn is 0.1 with the highest benzyl alcohol conversion of 63 %.